Correlation of photophysical parameters with macrocycle distortion in porphyrins with graded degree of saddle distortion - SENGE, MATHIAS (My University, 2010)
Different porphyrin conformations are believed to play a role in controlling the cofactor properties in natural tetrapyrrole-protein complexes. In order to study the correlation between macrocycle nonplanarity and physicochemical properties in detail, a series of six porphyrins with graded degree of macrocycle distortion was investigated. These conformationally designed porphyrins are based on the successive introduction of ?-ethyl groups into the tetraphenylporphyrin parent macrocycle and the degree of nonplanarity is dependent on the number and localization of the ?-ethyl meso-phenyl interactions. The electronic properties of the complete series of porphyrins were investigated in solution. It was found that the singlet and triplet properties depend not only on the out-of-plane distortion parameter but also on the type of central metal. Moreover, it was found that macrocycle distortion affects the singlet state properties significantly stronger than the triplet properties. In addition, the efficiency of energy transfer to molecular oxygen was investigated. It was shown that the singlet oxygen quantum yield depends strongly on the triplet state lifetime of the porphyrins, resulting in differences between the decrease of intersystem crossing and singlet oxygen quantum yield. The observed gradual change of electronic parameters of base free tetraphenylporphyrins with increasing deformation of the macrocycle indicates the validity of using conformationally designed porphyrins to fine-tune photophysical properties.
PUBLISHED
Keywords: tetraphenylporphyrins; tetraphenylporphyrins; Nanoscience & Materials